KINERJA PEMERINTAH DESA SOAKONORA DALAM PELAYANAN ADMINISTRASI KEPENDUDUKAN - M.Tonere Bakence; Ali Lating; Syarifuddin Usman (JOURNAL OF ETHNIC DIVERSITY AND LOCAL WISDOM, 2024)
ABSTRACT Observing the performance of the Soakonora Village Government in the process of providing population administration services to the community is still overshadowed by several problems, the most prominent problems are regarding employee discipline, time, skills and work spirit of the village government. The performance of the Soakonora village government still needs to improve to further increase productivity in providing services to the community. Most village officials do not have the competencies appropriate to the workload they bear, such as knowledge, skills and attitudes to complete the work optimally. Apart from that, the lack of work enthusiasm from village officials also results in performance in providing services being hampered and slow, this has an impact on the community who think that their administrative affairs are being deliberately ignored by the village government.